Awareness and associated factors of prepackaged food nutrition labels by college students in China: a cross-sectional study - Liu, Qian; Chen, Jinyi (Frontiers in Public Health, 2025)
BackgroundThe effective utilization of nutrition labels on prepackaged foods can facilitate the cultivation of healthful dietary behaviors among college students, thereby mitigating the risk of chronic non-communicable diseases. The study assessed the ability of college students in China’s economically and educationally highly developed provinces to use food nutrition labels and explored the associated factors affecting the awareness of food nutrition labels.MethodsA crosssectional study was conducted among college students enrolled in five higher education institutions in China. This study used a structured questionnaire method to collect data, descriptive statistics, and multivariate logistic regression to analyze and process the data.Results71.8% of college students had low awareness of food nutrition labeling. Awareness of food nutrition labeling was positively correlated with the degree of need (OR: 1.903; 95% Cl: 1.513–2.394), frequency of use (OR: 1.780; 95% Cl: 1.537–2.062), and trust (OR: 1.113; 95% Cl: 1.009–1.229), and was negatively correlated with the study of nutrition courses (OR: 0.655; 95% Cl: 0.528–0.812). The most important way for college students to acquire knowledge about food nutrition labeling was online videos (52.4%, n = 1,318). Furthermore, frequent utilization of nutritional labels in food choices, high demand, and high trust in food nutrition labels play a significant role in enhancing the awareness among college students in economically and educationally highly developed provinces.ConclusionIn light of our finding, we propose a reform of the existing nutrition education system to enhance nutritional awareness among college students through a more diversified set of instructional approaches and the implementation of compulsory nutrition education at an earlier stage. Leveraging popular media platforms to widely distribute professing nutritional information during daily public nutrition education is also advised.